Botanists of the twenty-first century roles, challenges and opportunities - Rakotoarisoa, Noëline R.; Blackmore, Stephen; Riera, Bernard (United Nations Educational, Scientific and Cultural Organisation (UNESCO), 2016)
This book is the compilation of presentations made at the Conference. At the beginning botany had a very wide scope which diversified and specialized in the twentieth century. Advances in technology (genetic engineering, geographic information systems, bioinformatics, modeling, etc.), the growing interest of the private sector, the recognition of local and indigenous knowledge, the need for teamwork and a multidisciplinary approach, the advent of citizen science, education and communication are among the topics that were discussed during the Conference.